Evaluation of kinematic methods of identifying gait events during running - Sinclair, J.; Edmundson, C. J.; Brooks, D.; Hobbs, S. J. (International Journal of Sports Science and Engineering, 2011)
Gait analysis necessitates the identification of foot-strike and toe-off events. This is characteristically achieved using force-platforms. However, when force data is unavailable, alternative methods are necessary. Several kinematic algorithms have emerged, but their effectiveness has yet to be validated for running gait. The rationale for this investigation is to contrast the timing of kinematically predicted events to those detected using force data. Synchronized vertical ground reaction force recordings and lower extremity kinematics of five trials from eleven participants running at 4.0ms-1+5% were recorded. From these eight kinematic algorithms, heel-strike and toe-off events were defined and compared using repeated-measures ANOVA`s. Heel-strike was most accurately determined using the Alton et al. (1998) O`Connor et al. (2007) and Dingwell et_al. (2001) methods. Toe-off was most accurately determined using the methods described by Dingwell et al. (2001) and Schace et al. (2003). Thus, an argument is presented for the utilization of these algorithms during running analysis when force data is unavailable.